Accountability in Malaysian Federal Statutory Bodies:influence of organizational culture, integrity, ethical climate, leadership and Audit Committee / Amirah Muhamad Nor - Muhamad Nor, Amirah (Institute of Graduate Studies, UiTM, 2013)
The research examined the concept, need and requirements for accountability in Malaysian Federal Statutory Bodies (FSBs) and how the independent variables such as organizational culture, ethical climate, transformationalleadership, integrity and existence of the Audit Committee affect accountability in the FSBs. This research adopts both a quantitative and qualitative approach to understand the three types of accountability such as Managerial Accountability, Fiduciary Accountability and Public Accountability. Questionnaires were posted to 118 FSBs in Malaysia. Five Face-to-face interviews were also conducted with the President of Malaysian Institute of Integrity, three senior management of Malaysian National Audit Department and Deputy Director General of Ministry of Higher Learning to gauge their perceptions relating to the research area. Four, structured interviews with four respondents from three FSBs were conducted. Out of 118 FSBs, only 68 (57.6%) FSBs responded to the survey by returning the questionnaires. The number of questionnaires returned to the researcher were 266 (45%) out of 590 questionnaires that were mailed or sent by hand. Data was analysed using Statistical Package for Social Science (SPSS Version 14). Suggestions and comments made by respondents on ways to improve accountability, integrity, organizational culture, ethical climate, leadership and audit committee were summarised…